UPAYA MENINGKATKAN HASIL BELAJAR TEKNIK DASAR SEPAK BOLA MELALUI PENDEKATAN BERMAIN KOMGIRBOL (KOMPETISI GIRING BOLA) DI KELAS V SD SALAMAN MLOYO SEMARANG (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to improve learning basic techniques of the game of football through fifth grade elementary komgirbol in Salaman Mloyo. The method used in this study is action research. Data collection techniques in this study consist of a class action practice test method, observation, and documentation. Data collected at each cycle of observation of the implementation of PTK is done by using descriptive analysis techniques percentage in learning activities. Acquisition cycle results in increased student responses to the application of the basic techniques of learning soccer game KOMGIRBOL (Competition Leads ball) in the second cycle. Seen also from the class average on the first cycle of 66.2 increased to 76.50 in the second cycle, whereas the results of classical completeness of 36.36% in the first cycle increased to 77.27% in cycle Il. Based on the percentage of acquisition cycles I and II can be taken conclusion use KOMGIRBOL game (Competition Leads Ball) can enhance learning basic techniques of soccer in the fifth grade students of SD Negeri Semarang Salaman Mloyo Academic Year 2013/2014..